MANAJEMEN ACTIVITY DAILY LIVING (ADL) UNTUK MENINGKATKAN KUALITAS TIDUR PADA PASIEN HIPERTENSI DI WILAYAH KERJA PUSKESMAS PAMPANG KOTA MAKASSAR - Riska Musa; Andi Mapanganro; Akbar Asraf; Wan Sulastri Emin (Jurnal Kesehatan, 2025)
Hypertension is one of the non-communicable diseases with a high prevalence and is known as the silent killer because it is often asymptomatic and causes serious complications. One of the main problems that hypertensive patients experience is sleep disturbances, which can worsen cardiovascular conditions. Activity Daily Living (ADL) management is an important non-pharmacological strategy to improve sleep quality while helping to control blood pressure. This research was conducted in the Pampang Health Center Working Area with the aim of finding out the effectiveness of the application of ADL management on the sleep quality of hypertensive patients. The research method used a case study on Mrs. T, a hypertensive patient with complaints of sleep disturbances. Interventions were carried out through structured daily activity arrangements including light mobilization, rest time management, low-salt healthy diet, and stress management. The results showed a significant improvement in sleep quality after regular application of ADL for three consecutive days. Before the intervention, the patient was only able to sleep 3–4 hours per night with frequent awakening, while after the intervention the sleep duration increased to 5–6 hours with a better quality and less frequent awakening. The application of ADL also reduces complaints of dizziness during activities and increases patients' independence in carrying out daily activities. In conclusion, ADL management has been shown to be effective as a nonpharmacological intervention to improve the sleep quality of hypertensive patients and can be applied routinely in community nursing care.